O Impacto Dos Recursos Do Ambiente Escolar No Desenvolvimento Das Habilidades Adaptativas Em Crianças E Adolescentes Com Síndrome De Williams - Arruda, Karina Dos Santos [UNIFESP] (2017)
Inclusive Education in Brazil has been engaged in valuable discussions about public policies, as well as pedagogical practices that favor the inclusion of students with disabilities. In the case of Intellectual Disability (DI), the demands of the resources for the effective inclusion of the students go far beyond the architectural adaptations of buildings; permeate teacher training, pedagogical practices and environmental resources that favor their full development. A condition of genetic origin associated with ID is Williams - SW Syndrome. This study aimed to evaluate the impact of the school's inclusive resources on the development of Adaptive Skills (communication, socialization, autonomy in activities of daily living) in a sample of children and adolescents with SW, from 7 to 18 years of age. age. To that end, those responsible responded to an inventory of adaptive skills (Vineland II) and schools were characterized according to the inclusive resources they offer students. The Inventory of Accessibility Resources and Inclusive Education was also created, which made it possible to quantify the resources offered in the school environment.